1996
DOI: 10.1159/000121035
|View full text |Cite
|
Sign up to set email alerts
|

Hyperf ractionated Craniospinal Radiation in Medulloblastoma

Abstract: From 1986 to 1991, 13 patients at Northwestern Memorial Hospital were entered onto a pilot study designed to test the feasibility of treating children with meduUoblastoma (11 patients) or primitive neuroectodermal tumors of the cerebral hemispheres (2 patients) with hyperfractionated craniospinal radiotherapy (HFxRT). Follow-up times ranged from 10 to 96 months with a median of 53 months. The patients were prospectively divided among three treatment arms depending on prior treatment history, if any, and degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In one study, low dose HFRT to 30 Gy CSI without chemotherapy resulted in an unacceptably high rate of relapse in the supratentorial brain and leptomeninges [18]. Other studies, however, confirmed the feasibility of the approach [19] and one suggested increased efficacy in high-risk patients [20]. The UKCCSG, HIT, and SFOP all plan to investigate the role of HFRT in average risk patients.…”
Section: Philosophy Results and Future Directions Of The Internatiomentioning
confidence: 99%
“…In one study, low dose HFRT to 30 Gy CSI without chemotherapy resulted in an unacceptably high rate of relapse in the supratentorial brain and leptomeninges [18]. Other studies, however, confirmed the feasibility of the approach [19] and one suggested increased efficacy in high-risk patients [20]. The UKCCSG, HIT, and SFOP all plan to investigate the role of HFRT in average risk patients.…”
Section: Philosophy Results and Future Directions Of The Internatiomentioning
confidence: 99%
“…The North American Groups have joined in an intergroup study comparing CCNU with cyclophosphamide combined with reduced radiation in both arms. The plans of the German Group are to ask a question regarding fractionation of radiotherapy (2,20). In any case, the efforts of multidisciplinary intense treatments have resulted in substantial improvement of survival in medu11oblastoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nach den Ergebnissen einer Pilotserie von Halperin et al [44] und Marymont et al [63] konnte in vielen Fällen durch eine hyperfraktionierte Bestrahlung eine anhaltende komplette Remission bei jedoch geringen Patientenzahlen erreicht werden (siehe Tabelle 1), sodass dieses radiotherapeutische Konzept in der HIT-2000-Studie prospektiv untersucht wird.…”
Section: Supratentorieller Pnetunclassified